Adsorption material and automotive carpet

By using silver-carpet inorganic porous adsorption materials and catalysts prepared in automotive carpets, the problem of difficulty in maintaining low formaldehyde, low odor and low bacteria for a long time during use of automotive carpets is solved, and automotive carpet products with low odor, low formaldehyde and antibacterial functions are achieved.

CN119701870APending Publication Date: 2025-03-28NOBO AUTOMOTIVE SYST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411902207.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

It is difficult for existing car carpets to maintain a low formaldehyde, low odor and low bacterial environment for a long time during use, and the existing treatment methods cannot meet consumers' needs for a long-term healthy environment in the car.

Method used

An adsorption material including 70% to 80% silver-loaded inorganic porous adsorption material, 8% to 10% catalyst and 12% to 20% water is used. Through high temperature activation and uniform coverage of the catalyst, a material with good adsorption and sterilization functions is prepared, and added to the car carpet to capture formaldehyde and odor molecules, and the formaldehyde is decomposed through the catalyst.

Benefits of technology

It realizes the low-odor, low formaldehyde and antibacterial functions of car carpets, maintains a healthy environment in the car for a long time, and meets consumers' long-term low formaldehyde and low odor in the car.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701870A_ABST
    Figure CN119701870A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of automotive carpets, and particularly provides an adsorption material and an automotive carpet. The adsorption material comprises the following components in percentage by mass: 70%-80% of a silver-loaded inorganic porous adsorption material, 8%-10% of a catalyst and 12%-20% of water. According to the adsorption material, the catalyst is added into the silver-loaded inorganic porous adsorption material to prepare the material with good adsorption performance, the material is added into the automobile carpet, formaldehyde and peculiar smell molecules released by the carpet can be captured through the adsorption effect of the inorganic porous adsorption material, the formaldehyde is decomposed by the catalyst, and meanwhile, the peculiar smell can be removed through the adsorption effect of the inorganic porous adsorption material. The silver and the catalyst have a degerming function and can remove bacteria bred on the carpet, so that the automobile carpet has low-odor, low-formaldehyde and antibacterial functions and is beneficial to improving the environmental quality in an automobile cabin, and the adsorption material which is suitable for being added into the automobile carpet to reduce the release amount of harmful molecules of the automobile carpet is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of automobile carpets, and in particular to an adsorption material. In addition, the present invention also relates to an automobile carpet. Background Art

[0002] As people's health requirements continue to improve, the environment in the car cabin is also receiving more and more attention from consumers. Formaldehyde, as an important pollutant in the car cabin environment, is irritating and pathogenic. The odor in the cabin will make the driver and passengers feel uncomfortable. At the same time, the number of bacteria also directly affects the health of the driver and passengers. Low formaldehyde, low odor and low bacteria count have become the three major demands of consumers for the health of the car cabin.

[0003] As one of the important parts in the car cabin, car carpet has a large area and is directly exposed to the cabin environment, so it contributes a lot to the formaldehyde and odor in the cabin. At the same time, car carpet is easy to be attached with foreign matter, food residues, etc., and is not easy to clean, which makes it very easy to breed bacteria.

[0004] In the prior art, the way to reduce the formaldehyde release and odor of carpets is generally to do it after the carpet products come off the production line, usually by high-temperature baking, ventilation and ozone sterilization of the car carpets. The above methods have the following disadvantages:

[0005] 1. After the product is off the production line, it is baked at high temperature and ventilated, which can reduce formaldehyde and odor in a short time. However, because formaldehyde and odor molecules are a continuous generation process, when the carpet is loaded on the car and the car is sold, during the years to more than ten years after the consumer purchases the car, formaldehyde and odor are continuously generated, which cannot meet the user's demand for long-term low odor and low formaldehyde in the car;

[0006] 2. Using ozone sterilization can reduce the number of bacteria on car carpets in the short term. However, after consumers buy and use the car, as the driver and passengers repeatedly get in and out of the car, the soles of their shoes touch the carpet, and the carpet is easily attached to foreign matter such as dirt, sewage, and food residues, causing the carpet to still breed a large number of bacteria. Summary of the invention

[0007] In view of this, the present invention aims to provide an adsorption material, so as to provide an adsorption material suitable for being added to a car carpet to reduce the amount of harmful molecules released from the car carpet.

[0008] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0009] An adsorbent material comprising the following components in mass ratio:

[0010] 70% to 80% of silver-carrying inorganic porous adsorption material, 8% to 10% of catalyst, and 12% to 20% of water.

[0011] Furthermore, the silver-loaded inorganic porous adsorption material is silver-loaded nutshell activated carbon with a particle size of 60-80 meshes, and the silver-loaded amount of the silver-loaded nutshell activated carbon is 0.8wt%-1.0wt%.

[0012] Furthermore, the catalyst comprises powdered titanium dioxide, and / or the water is pure water.

[0013] Furthermore, the adsorbent material is prepared by the following method:

[0014] The silver-loaded inorganic porous adsorption material is activated at high temperature; the catalyst and the water are mixed and stirred to form a suspension, and the suspension is coated on the surface of the silver-loaded inorganic porous adsorption material, and then air-dried; the air-dried silver-loaded inorganic porous adsorption material is dried.

[0015] Further, the high temperature activation is carried out at 140° C. to 180° C. and lasts for 3 to 5 hours; and / or the drying treatment is carried out at 100° C. to 140° C. and lasts for 4 to 8 hours.

[0016] Furthermore, the coating of the suspension onto the surface of the silver-carrying inorganic porous adsorption material is performed multiple times, and after each coating operation is completed, the suspension is air-dried for more than 25 minutes before the next coating operation is performed.

[0017] Furthermore, 20% to 30% of the suspension is taken each time to coat the surface of the silver-carrying inorganic porous adsorption material until the suspension is used up.

[0018] Compared with the prior art, the present invention has the following advantages:

[0019] The adsorption material of the present invention is prepared by adding a catalyst to a silver-carrying inorganic porous adsorption material to form a material with good adsorption performance. The material is added to a car carpet. The formaldehyde and odor molecules released by the carpet can be captured through the adsorption effect of the inorganic porous adsorption material, and the formaldehyde is decomposed by the catalyst. At the same time, the silver and the catalyst themselves have a sterilization function and can remove bacteria that grow on the carpet, so that the car carpet has low odor, low formaldehyde and antibacterial functions, which is beneficial to improving the environmental quality in the car cabin. Therefore, an adsorption material suitable for being added to the car carpet to reduce the release amount of harmful molecules from the car carpet is provided.

[0020] In addition, the silver-loaded nutshell activated carbon is made of fruit core shell activated carbon with high strength and large adsorption capacity as raw material and loaded with silver. It has the excellent functions of sterilization, antibacterial, and removal of odor, odor and trace toxic and harmful substances in water; the silver-loaded nutshell activated carbon with a set particle size and a set content of silver can ensure that the silver-loaded inorganic porous adsorption material has good formaldehyde and odor molecule capture performance. The catalyst uses titanium dioxide, and pure water is mixed and stirred to form a suspension, which is convenient for evenly covering the surface of the silver-loaded inorganic porous adsorption material with titanium dioxide, so that the silver-loaded inorganic porous adsorption material can play a better adsorption role. Moreover, titanium dioxide itself, as a metal oxide, also has a good sterilization effect. The combination of titanium dioxide and silver-loaded nutshell activated carbon can give full play to the harmful responsible adsorption and sterilization capabilities of the adsorption material in the car carpet.

[0021] In addition, the catalyst is made into a suspension using water and then applied to the silver-loaded inorganic porous adsorption material that has been activated at high temperature, so that the catalyst can be fully and evenly distributed on the silver-loaded inorganic porous adsorption material, so that the catalyst can better stimulate the adsorption performance of the silver-loaded inorganic porous adsorption material; the adsorption material prepared by drying the silver-loaded inorganic porous adsorption material can have good adsorption and antibacterial capabilities.

[0022] Another object of the present invention is to provide an automobile carpet, wherein the automobile carpet is provided with an adsorption layer, and the adsorption layer is coated with the adsorption material described in the present invention.

[0023] Furthermore, the automobile carpet further comprises a fabric layer, a film layer and a base layer, wherein the fabric layer, the adsorption layer, the film layer and the base layer are sequentially arranged from top to bottom and composited into one.

[0024] Furthermore, the fabric layer is made of PET fabric, and / or the film layer is made of PE / PA / PE co-extruded composite film, and / or the base layer is made of ES fiber felt.

[0025] The automobile carpet of the present invention uses the adsorption material as the adsorption layer in the automobile carpet, making full use of the advantages of the automobile carpet's large area and large extension space, and can achieve complete coverage of the automobile carpet, so as to fully adsorb various harmful molecules such as formaldehyde and odor released by the carpet, thereby providing an automobile carpet product that can improve the environment in the automobile cabin. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The accompanying drawings, which constitute part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention. The directional terms such as front and back, up and down, etc. involved therein are only used to indicate relative positional relationships and do not constitute improper limitations on the present invention. In the accompanying drawings:

[0027] Figure 1 This is a schematic diagram of the preparation process of the adsorption material according to an embodiment of the present invention;

[0028] Figure 2 This is a schematic diagram of the cross-sectional structure of an automobile carpet according to an embodiment of the present invention;

[0029] Figure 3 This is a schematic diagram of the process flow of manufacturing an automobile carpet according to an embodiment of the present invention;

[0030] Description of reference numerals:

[0031] 1. Fabric layer; 2. Adsorption layer; 3. Film layer; 4. Base layer. DETAILED DESCRIPTION

[0032] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0033] In the description of the present invention, it should be stated that if terms indicating directions or positional relationships such as "up, down, left, right, front, back, inside, outside" appear, they are based on the directions or positional relationships shown in the drawings and are only for the convenience of describing the present invention. They do not indicate or imply that the device or element referred to must have a specific direction, be constructed or operate in a specific direction. Therefore, they cannot be understood as limitations on the present invention.

[0034] The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with embodiments.

[0035] Embodiment 1

[0036] This embodiment relates to an adsorbent material suitable for being added to a car carpet to reduce the amount of harmful molecules released from the car carpet. An exemplary preparation process of the adsorbent material is as follows: Figure 1 shown.

[0037] In general, the adsorbent material comprises the following components in mass ratio:

[0038] 70% to 80% of silver-carrying inorganic porous adsorption material, 8% to 10% of catalyst, and 12% to 20% of water.

[0039] It should be pointed out that based on the above-mentioned overall configuration requirements, the technical solution of the present invention can adopt a variety of different ratio schemes. For example, the configuration amount of the above-mentioned catalyst can be 8%, 9%, 10% or any other value between 8% and 10%; the ratio of the silver-loaded inorganic porous adsorption material can also be appropriately adjusted between 70% and 80%. For the parts required for the implementation of the overall scheme but not involved in the above-mentioned overall setting, reasonable and flexible designs can be made with reference to the mature setting means in the field, the actual situation during implementation, etc. The specific implementation scheme described below in this embodiment is only one of the better solutions that can be formed by the above-mentioned various combinations and their changes. In actual implementation, those skilled in the art can make flexible adjustments and improvements based on the actual situation. Obviously, the many solutions that can be formed by the above-mentioned various specific forms of combination and its changes, as well as the specific implementation scheme of this embodiment, are all within the scope of protection of the present invention.

[0040] Specifically, in this embodiment, the silver-carrying inorganic porous adsorption material preferably adopts silver-carrying nutshell activated carbon with a particle size of 60-80 mesh, so that its specific surface area is ≥1200m 2 / g, and the silver loading of the silver-loaded nutshell activated carbon is controlled between 0.8wt% and 1.0wt%. The silver-loaded nutshell activated carbon is made of fruit core shell activated carbon with high strength and large adsorption capacity as raw material and loaded with silver. It has excellent functions of sterilization and inhibition, and removal of odor, odor and trace toxic and harmful substances in water; the silver-loaded nutshell activated carbon with a set particle size and loaded with a set content of silver can ensure that the silver-loaded inorganic porous adsorption material has good formaldehyde and odor molecule capture performance.

[0041] The catalyst is preferably powdered titanium dioxide, with a particle size between 22500 mesh and 28000 mesh. The water is preferably purified water, and the quality control requirements for purified water include: conductivity <10us / cm (25°C), total colony count ≤20cfu / mL, coliform group ≤3MPN / 100mL, and mold, yeast and pathogenic bacteria (Salmonella, Shigella, Staphylococcus aureus) must not be detected.

[0042] The catalyst uses titanium dioxide, which is mixed and stirred with pure water to form a suspension, so that the titanium dioxide can be evenly covered on the surface of the silver-carrying inorganic porous adsorption material, so that the silver-carrying inorganic porous adsorption material can play a better adsorption role. Moreover, titanium dioxide itself, as a metal oxide, also has a good sterilization effect. The combination of titanium dioxide and silver-carrying nutshell activated carbon can give full play to the harmful adsorption and sterilization capabilities of the adsorption material in the car carpet.

[0043] Based on the configuration of the above components, the adsorbent material of the present invention can be prepared by the following method:

[0044] S1. Activating the silver-carrying inorganic porous adsorption material at high temperature;

[0045] S2, mixing the catalyst and the water to form a suspension, and coating the suspension on the surface of the silver-carrying inorganic porous adsorption material, and then air-drying;

[0046] S3, drying the air-dried silver-loaded inorganic porous adsorption material.

[0047] The catalyst is made into a suspension using water, and then applied to the silver-loaded inorganic porous adsorption material that has been activated at high temperature, so that the catalyst can be fully and evenly distributed on the silver-loaded inorganic porous adsorption material, so that the catalyst can better stimulate the adsorption performance of the silver-loaded inorganic porous adsorption material; the adsorption material prepared by drying the silver-loaded inorganic porous adsorption material can have good adsorption and antibacterial capabilities.

[0048] Preferably, the high temperature activation in step S1 is carried out at 140°C to 180°C and lasts for 3 to 5 hours. The drying treatment in step S3 is carried out at 100°C to 140°C and lasts for 4 to 8 hours. By reasonably controlling the temperature and time conditions of activation and drying, the process effects of the activation and drying processes can be guaranteed, and the final performance and quality of the manufactured material can be ensured.

[0049] Moreover, the coating operation corresponding to step S2 is preferably carried out in multiple times; that is, the above-mentioned suspension is coated on the surface of the silver-loaded inorganic porous adsorbent material in multiple times; and after each coating is completed, it is air-dried for more than 25 minutes before the next coating operation. Specifically, 20% to 30% of the suspension can be used each time to coat the surface of the silver-loaded inorganic porous adsorbent material until the above-mentioned suspension is used up. Coating the catalyst suspension on the silver-loaded inorganic porous adsorbent material in multiple times can further improve the uniformity of the catalyst on the surface of the silver-loaded inorganic porous adsorbent material, ensure that the surface of the silver-loaded inorganic porous adsorbent material is completely covered by the catalyst, thereby giving full play to the catalytic effect of the catalyst in the silver-loaded inorganic porous adsorbent material.

[0050] Based on the above overall configuration and preparation process ideas, combined with Figure 1 As shown, when preparing and processing the adsorption material, the following specific process scheme can be adopted.

[0051] S1. Put the silver-loaded nutshell activated carbon material into an oven and activate it at 160°C for 4 hours;

[0052] S21, putting a set amount of titanium dioxide powder in a glass beaker, pouring a set amount of pure water into the beaker, and then stirring with an electric stirrer at a speed of 2300-2500 r / min for 2 min to obtain a titanium dioxide suspension;

[0053] S22, taking 20%-30% of the titanium dioxide suspension prepared in step S21, uniformly coating it on the surface of the silver-carrying nutshell activated carbon material to form a thin film, and air-drying it for 30 minutes to obtain titanium dioxide-coated silver-carrying nutshell activated carbon;

[0054] S23, repeating step S22 until the titanium dioxide suspension prepared in step S21 is consumed;

[0055] S3, placing the silver-loaded nutshell activated carbon coated with titanium dioxide suspension obtained in step S23 in an oven at 120° C. and drying for 6 hours, taking it out and cooling it to room temperature to obtain a finished product of titanium dioxide-coated silver-loaded nutshell activated carbon material (i.e., finished adsorption material).

[0056] The finished products can be sealed in PE bags and can be used whenever needed during the processing of automotive carpets.

[0057] In summary, the adsorption material of this embodiment is prepared by adding a catalyst to a silver-loaded inorganic porous adsorption material to form a material with good adsorption performance. The material is added to a car carpet. The formaldehyde and odor molecules released by the carpet can be captured by the adsorption effect of the inorganic porous adsorption material, and the formaldehyde is decomposed by the catalyst. At the same time, the silver and the catalyst themselves have a sterilization function, which can remove bacteria that grow on the carpet, so that the car carpet has low odor, low formaldehyde and antibacterial functions, which is beneficial to improving the environmental quality in the car cabin. Therefore, an adsorption material suitable for adding to a car carpet to reduce the release of harmful molecules from the car carpet is provided.

[0058] Embodiment 2

[0059] This embodiment relates to an automobile carpet, in which an adsorption layer 2 is provided, and the adsorption layer 2 is coated with the adsorption material provided in Embodiment 1. By adding the adsorption material to the automobile carpet and using it as the adsorption layer 2 in the automobile carpet, the advantages of the automobile carpet having a large area and a large extension space are fully utilized, and the automobile carpet can be completely covered, so that various harmful molecules such as formaldehyde and odor released by the carpet can be fully adsorbed, thereby providing an automobile carpet product that can improve the environment in the car cabin.

[0060] Regarding the specific configuration of the car carpet, there are of course a variety of different structural solutions to choose from. In this embodiment, Figure 2As shown, the car carpet also includes a fabric layer 1, a film layer 3 and a base layer 4, and the fabric layer 1, the adsorption layer 2, the film layer 3 and the base layer 4 are sequentially arranged from top to bottom and composited into one. The adsorption layer 2 is arranged between the fabric layer 1 and the film layer 3, and the adsorption layer 2 is firmly fixed in the carpet by virtue of the adhesive property of the film layer 3; at the same time, the adsorption layer 2 can well adsorb harmful molecules released from the film layer 3 and the base layer 4 below, as well as the fabric layer 1 above, and can exert an antibacterial effect on the fabric layer 1 nearby.

[0061] There are of course many different options for the specific materials used in each layer. Preferably, the fabric layer 1 of this embodiment uses PET fabric, the film layer 3 uses PE / PA / PE co-extruded composite film, and the base layer 4 uses ES fiber felt. The adsorption layer 2 uses the adsorption material of Example 1, which is coated on the fabric layer 1.

[0062] Based on the above overall configuration of the car carpet, combined with Figure 3 As shown, the automotive carpet of this embodiment can be manufactured and processed by the following process:

[0063] S1, carpet blank compounding: arranging the fabric layer 1, the adsorption layer 2, the film layer 3 and the base layer 4 in order from top to bottom, and compounding and forming them to form a carpet blank;

[0064] S2, heating the blanket composite sheet, and placing the heated blanket in a hot pressing mold to form a semi-finished automotive carpet;

[0065] S3, foaming on the back of the semi-finished carpet;

[0066] S4. The foamed carpet semi-finished product is water-cut and assembled with accessories to complete the production of the automotive carpet product.

[0067] The finished carpet products can be inspected and put into storage.

[0068] Based on the component ratio and preparation process principle of the adsorption material provided in Example 1 and the processing process setting of the automobile carpet provided in Example 2, the following comparative experiment is carried out by adjusting the component ratio and adjusting the process parameters within the set process parameter range; and the carpet products made from the experimental examples and comparative examples under different ratios are tested, and the following experimental analysis can be obtained.

[0069] The contents of the components in the experimental examples 1-15 and the comparative examples are shown in Table 1 below:

[0070] Table 1:

[0071]

[0072] The car carpet products prepared in the comparative example and experimental examples 1-15 were tested for formaldehyde content, odor and E. coli colony count. The detection method and the calculation method of "formaldehyde removal rate", "odor improvement effect" and "antibacterial rate" in Table 2 below are as follows:

[0073] 1. Formaldehyde detection method: (based on the bag method in GB / T 39897-2021, the national standard of the People's Republic of China, using a 2000L sampling bag):

[0074] Formaldehyde removal rate = [(formaldehyde detection value of the experimental example - formaldehyde detection value of the comparative example) / formaldehyde detection value of the comparative example] × 100%.

[0075] 2. Odor detection method: (based on the dry method in the PV3900-2000 standard released by Volkswagen)

[0076] Odor improvement effect = experimental example odor level - comparative example odor level; wherein, odor level refers to odor concentration, and the higher the level, the stronger the odor.

[0077] 3. Escherichia coli colony count detection method: (Based on GBT 20944.3-2008 standard issued by the General Administration of Quality Supervision, Inspection and Quarantine of the People's Republic of China)

[0078] Bacterial inhibition rate = [(the number of E. coli colonies in the experimental example - the number of E. coli colonies in the comparative example) / the number of E. coli colonies in the comparative example] × 100%.

[0079] The final test verification results are shown in Table 2:

[0080] Table 2:

[0081]

[0082]

[0083] Through the above comparative tests and analysis, it can be seen that compared with the comparative example (i.e. the control group: the original state, without the antibacterial car carpet with low odor and low formaldehyde), the formaldehyde and odor levels of each experimental example are reduced, and the antibacterial rate is improved.

[0084] Comparing Experimental Examples 2-15 with Experimental Example 1 shows that the antibacterial rate of the silver-loaded nutshell activated carbon material alone did not reach the optimal level (antibacterial rate > 99.99%). In Experimental Examples 2-15, the antibacterial rate effect has reached the optimal level. As the proportion of nutshell activated carbon material increases, the formaldehyde removal rate also tends to increase, and the odor level tends to decrease. However, when the proportion of nutshell activated carbon material reaches 74%, the improvement of formaldehyde and odor is no longer obvious when the proportion of nutshell activated carbon material is increased (refer to Experimental Examples 9-15). In terms of comprehensive cost and effect, Experimental Example 7 is relatively optimal.

[0085] In summary, in the blanket coating production process of the automotive carpet of the present invention, a layer of the adsorbent material of the present invention is evenly coated on the PET fabric, and then compounded with the PE / PA / PE co-extruded composite film and the ES fiber felt, the fruit shell activated carbon adsorbs formaldehyde and odor molecules, the titanium dioxide decomposes formaldehyde, the coated titanium dioxide has strong oxidizing properties, and the silver has a bactericidal effect, both of which can kill bacteria. Through the above measures, the automotive carpet product can have low odor, low formaldehyde and antibacterial functions.

[0086] Furthermore, unlike the treatment method in which the manufacturer bakes, ventilates and uses ozone to sterilize the car carpet after the product comes off the production line (this traditional method can only temporarily reduce the product odor, formaldehyde and bacteria count), the present invention, without changing other production processes of the original carpet, adds a layer of adsorption material to the process link, and adds the silver-loaded nutshell activated carbon material coated with titanium dioxide to the interlayer of the carpet, so that the car carpet has low odor, low formaldehyde and antibacterial functions. At the same time, after the consumer purchases the car, because the car carpet is used by the consumer, it can still maintain the above-mentioned ability to absorb harmful molecules and inhibit bacteria.

[0087] The above description is only a preferred embodiment of the present invention. The detailed explanation of the configuration, the examples of the specific structural setting forms, or the description of the assembly connection mode, etc., are all for the purpose of sufficient disclosure so that those skilled in the art can better implement the present invention, but are not intended to limit the protection scope of the present invention. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An adsorption material, characterized in that: The composition includes the following components in mass ratio: 70% to 80% of silver-carrying inorganic porous adsorption material, 8% to 10% of catalyst, and 12% to 20% of water.

2. The adsorption material according to claim 1, characterized in that: The silver-loaded inorganic porous adsorption material is silver-loaded nutshell activated carbon with a particle size of 60-80 meshes, and the silver-loaded amount of the silver-loaded nutshell activated carbon is 0.8wt%-1.0wt%.

3. The adsorption material according to claim 1, characterized in that: The catalyst comprises powdered titanium dioxide, and / or the water is pure water.

4. The adsorption material according to any one of claims 1 to 3, characterized in that The adsorbent material is prepared by the following method: Activating the silver-carrying inorganic porous adsorption material at high temperature; The catalyst and the water are mixed and stirred to form a suspension, and the suspension is coated on the surface of the silver-carrying inorganic porous adsorption material, followed by air drying; The air-dried silver-loaded inorganic porous adsorption material is dried.

5. The adsorption material according to claim 4, characterized in that: The high temperature activation is performed at 140° C. to 180° C. and lasts for 3 to 5 hours; and / or the drying treatment is performed at 100° C. to 140° C. and lasts for 4 to 8 hours.

6. The adsorption material according to claim 4, characterized in that: The coating of the suspension onto the surface of the silver-carrying inorganic porous adsorption material is performed multiple times, and after each coating operation is completed, the suspension is air-dried for more than 25 minutes before the next coating operation is performed.

7. The adsorption material according to claim 6, characterized in that: Each time, 20% to 30% of the suspension is used to coat the surface of the silver-carrying inorganic porous adsorption material until the suspension is used up.

8. An automobile carpet, characterized in that: An adsorption layer (2) is provided in the automobile carpet, and the adsorption layer (2) is coated with the adsorption material according to any one of claims 1 to 7.

9. The automotive carpet according to claim 8, characterized in that: The automobile carpet further comprises a fabric layer (1), a film layer (3) and a base layer (4); the fabric layer (1), the adsorption layer (2), the film layer (3) and the base layer (4) are arranged in sequence from top to bottom and are composited into one.

10. The automotive carpet according to claim 9, characterized in that: The fabric layer (1) is made of PET fabric, and / or the film layer (3) is made of PE / PA / PE co-extruded composite film, and / or the base layer (4) is made of ES fiber felt.